Egg quality parameter of Naked Neck chicken and commercial layer strains in Bangladesh - Hasan, Md Kamrul; Mamun, Hasnat; Hossain, Md Nazmul; Rahman, Md Anisur (Asian Journal of Medical and Biological Research, 2020)
Egg quality parameter is important for determination of egg quality, grading of egg and pricing. To conduct this study, 50 eggs of Hy-line Brown, 50 eggs of ISA Brown, 50 eggs of Saver-579 Brown and 50 eggs of Novogen Brown and 50 eggs of Naked Neck were collected from different poultry farms of Sylhet. Egg shape index (ESI) of Hy-line Brown, ISA Brown, Saver-579, Novogen Brown and Naked Neck were 78.86±1.24, 78.85±0.5, 78.45±1.20, 81.43±1.56 and 76.85±0.92 respectively. Egg weight of Hy-line Brown, ISA Brown, Saver-579, Novogen Brown and Naked Neck were 62.48±1.54g, 61.89±1.2g, 61.41±1.47g, 64.76±1.37g and 37.45±1.2g respectively. Yolk weight of Hy-line Brown, ISA Brown, Saver-579, Novogen Brown and Naked Neck were 18.09±0.62g, 18.26±0.29g, 19.33±0.32g, 19.73±0.21g and 15.12±0.48g respectively. Among the different strains/breed, Novogen Brown has the highest value and Naked Neck has the lowest value for ESI, egg weight and yolk weight. So that the grading value of Novogen Brown has the highest among other strain/breed. Future research is necessary to see the internal egg quality parameter (albumen index, yolk index, Haugh Units (HU) and yolk colour) of different strain/breed, which will help for grading of egg. Asian J. Med. Biol. Res. September 2020, 6(3): 514-518